Does evaluation of the ligamentous compartment enhance diagnostic utility of sacroiliac joint MRI in axial spondyloarthritis?. Issue 1 (December 2015) - Weber, Ulrich; Maksymowych, Walter; Chan, Stanley; Rufibach, Kaspar; Pedersen, Susanne; Zhao, Zheng; Zubler, Veronika; Østergaard, Mikkel; Lambert, Robert
Abstract Introduction Inflammation of the sacroiliac joints (SIJ) is a fundamental clinical feature of axial spondyloarthritis (SpA). The anatomy of the irregularly shaped SIJ is complex with an antero-inferior cartilaginous compartment containing central hyaline and peripheral fibrocartilage, and a dorso-superior ligamentous compartment. Several scoring modules to systematically assess SIJ magnetic resonance imaging (MRI) in SpA have been developed. Nearly all of them are based on the cartilaginous joint compartment alone. However, there are only limited data about the frequency of inflammatory lesions in the ligamentous compartment and their potential diagnostic utility in axial SpA. We therefore aimed to evaluate the ligamentous compartment on sacroiliac joint MRI for lesion distribution and potential incremental value towards diagnosis of SpA over and above the traditional assessment of the cartilaginous compartment alone. Methods Two independent cohorts of 69 and 88 consecutive back pain patients ≤50 years were referred for suspected SpA (cohort A) or acute anterior uveitis plus back pain (cohort B). Patients were classified according to rheumatologist expert opinion based on clinical, radiographic and laboratory examination as having nonradiographic axial SpA (nr-axSpA; n = 51), ankylosing spondylitis (n = 34), or nonspecific back pain (NSBP; n = 72). Five blinded readers assessed SIJ MRI globally for presence/absence of SpA. Bone marrow edema (BME) and fat metaplasia were recorded in the cartilaginous and ligamentous compartment. The incremental value of evaluating the ligamentous additionally to the cartilaginous compartment alone for diagnosis of SpA was graded qualitatively. We determined the lesion distribution between the two compartments, and the impact of the ligamentous compartment evaluation on diagnostic utility. Results MRI bone marrow lesions solely in the ligamentous compartment in the absence of lesions in the cartilaginous compartment were reported in just 0–2.0/0–4.0 % (BME/fat metaplasia) of all subjects. Additional assessment of the ligamentous compartment was regarded as essential for diagnosis in 0 and 0.6 %, and as contributory in 28.0 and 7.7 % of nr-axSpA patients in cohorts A and B, respectively. Concomitant BME in both compartments was evident in 11.6–42.0 % of nr-axSpA and 2.1–2.4 % of NSBP patients. Conclusion Assessing the ligamentous compartment on SIJ MRI provided no incremental value for diagnosis of axial SpA. However, concomitant BME in both compartments may help discriminate nr-axSpA from NSBP.